Tari Gadung Melati Sebagai Lambang Sanggar Seni Semara Ratih, Ubud, Gianyar - Ida Ayu Putu Eka Purnama Dewi; Gusti Ayu Ketut Suandewi; Suminto Suminto (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2023)
Semara Ratih Art Studio is one of the studios in Ubud, Gianyar Regency. Gadung Melati Dance is a welcoming dance that is a symbol of the Semara Ratih Art Studio. This dance is danced by women who are danced by 6 dancers. The costumes in this dance tend to be yellow and green. The property used in the Gadung Melati Dance is the canang rebong. This dance is accompanied by gamelan semarandana. The method used in the research of Gadung Melati Dance is a qualitative method, with the techniques used in data collection are observation, interviews, documentation, library studies and data analysis. From the results of data analysis and findings in the Gadung Melati Dance field, there are several backgrounds taken from the conditions that exist in plant life. The creation dance entitled Gadung Melati Dance is a welcoming dance inspired by flora/plants. The Gadung Melati dance is the first welcoming dance that uses a Tandak interpreter and in its movement uses a Sisia crew. after this paper was formed because he wanted to convey the message of how to preserve Balinese art. Keywords: Gadung Melati, Welcome Dance, Symbols